1975
DOI: 10.1159/000260180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monofluorophosphate on the Pathways followed by Cariogenic Agents

Abstract: The purpose of this study was to investigate the ultra structural changes in human enamel – untreated and pre-treated with Na2FPO3 – after an artificial carious attack. With the scanning electronmicroscope the influence of local fluoride application on surface topography and on the caries lesions in cross-sections was investigated. The results show that in Na2FPO3 pre-treated specimen the prism core dissolved faster than the interprismatic areas. The experiments indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In case of the hydrochloric and phosphoric acid treatments an apparent preference of dissolution is present, which accounts for the greater surface roughness in these two cases. The SEM photographs of the investigated samples correspond to those shown by Gwinnet [1971], Boyde et al [1978], Silverstone [1975] and Jongebloed et al [1975]. The surface roughness values obtained are in good agreement with the values produced by Dennison et al [1978] in comparable experiments.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…In case of the hydrochloric and phosphoric acid treatments an apparent preference of dissolution is present, which accounts for the greater surface roughness in these two cases. The SEM photographs of the investigated samples correspond to those shown by Gwinnet [1971], Boyde et al [1978], Silverstone [1975] and Jongebloed et al [1975]. The surface roughness values obtained are in good agreement with the values produced by Dennison et al [1978] in comparable experiments.…”
Section: Methodssupporting
confidence: 85%
“…The results of figure 7 show that the sur face layer of bovine enamel is affected only slightly by the potassium lactate buffer [Jongebloed et al, 1975], This demineraliz ing solution has a nonpreferential dissolu tion character; the material is evenly taken off and to a much smaller extent than in the case of hydrochloric and orthophosphoric acid. Examination of cross sections, which were not part of this investigation, show that although apparently not much hap pened at the surface a change of subsurface morphology occurred.…”
Section: Discussionmentioning
confidence: 94%
“…Previous investigators have suggested that principal diffusion pathways were along rod peripheries and larger enamel defects [Mortimer and Tranter, 1971;Scott et al, 1974;Jongebloed et al, 1975;Haikel et al 1983;Theunset al, 1982;Ingram and Fejerskov, 1984]. Christoffersen and A rends [1982] based their interpretation of subsur face formation on the assumption of the small holes produced in surface enamel being 0.1-0.5 /xm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Mortimer and Tranter, 1971;Jongebloed et al, 1975], If one as sumes the prisms to be cylindrically shaped, parallel oriented and packed at maximum density, the interprismatic material corre sponds to 21.5 vol#/o of the total enamel. During later stages of demineralization the prisms will be attacked also, radially and ir regularly.…”
Section: Discussionmentioning
confidence: 99%